Mathematical Model for Estimating Char Production Rates Derived From the Pyrolysis of Rice Hulls and Corn Cobs - ADAMON, David G. F.; FAGBEMI, LATIF ADÉNIYI; BENSAKHRIA, Ammar; SANYA, EMILE A. (My University, 2017)
There is a need to promote sustainable energy resources that balance consumer fuel demands and minimize environmental impacts. An obvious solution to this problem is renewable energy fuels, such as biomass. Corn cobs and rice hulls are abundant resources for biofuel production in the country of Benin. The objective of this study was to estimate the rate of char production during the pyrolysis phase of the gasification reaction. A mathematical model was developed based on the pyrolysis data at isothermic conditions to predict the char rates of corn cobs and rice hulls at different temperatures. Curve fittings of the data were performed using MATLAB 7.0 software using Newton’s method. Predictions from the model confirmed the influence of temperature on the char rates of the examined biomasses, as well as the distinguishable stages observed during pyrolysis. The char yield from rice hulls was greater than from corn cobs regardless of the pyrolysis temperature
Keywords: Biomass - Char – Pyrolysis – Mathematical model.